Baseline characteristics and enrichment results from the SONAR trial. Issue 8 (1st May 2018) - Heerspink, Hiddo J.L.; Andress, Dennis L.; Bakris, George; Brennan, John J.; Correa‐Rotter, Ricardo; Hou, Fan Fan; Kitzman, Dalane W.; Kohan, Donald; Makino, Hirofumi; McMurray, John; Perkovic, Vlado; Tobe, Sheldon; et al.
Abstract : Aim: The SONAR trial uses an enrichment design based on the individual response to the selective endothelin receptor antagonist atrasentan on efficacy (the degree of the individual response in the urinary albumin‐to‐creatinine ratio [UACR]) and safety/tolerability (signs of sodium retention and acute increases in serum creatinine) to assess the effects of this agent on major renal outcomes. The patient population and enrichment results are described here. Methods: Patients with type 2 diabetes with an estimated glomerular filtration rate (eGFR) within 25 to 75 mL/min/1.73 m 2 and UACR between 300 and 5000 mg/g were enrolled. After a run‐in period, eligible patients received 0.75 mg/d of atrasentan for 6 weeks. A total of 2648 responder patients in whom UACR decreased by ≥30% compared to baseline were enrolled, as were 1020 non‐responders with a UACR decrease of <30%. Patients who experienced a weight gain of >3 kg and in whom brain natriuretic peptide exceeded ≥300 pg/mL, or who experienced an increase in serum creatinine >20% (0.5 mg/dL), were not randomized. Results: Baseline characteristics were similar for atrasentan responders and non‐responders. Upon entry to the study, median UACR was 802 mg/g in responders and 920 mg/g in non‐responders. After 6 weeks of treatment with atrasentan, the UACR change in responders was −48.8% (95% CI, −49.8% to −47.9%) and in non‐responders was −1.2% (95% CI, −6.4% to 3.9%). Changes in other renal risk markers were similar between responders and non‐responders except for a marginally greater reduction in systolic blood pressure and eGFR in responders. Conclusions: The enrichment period has successfully identified a population with a profound UACR reduction without clinical signs of sodium retention in whom a large atrasentan effect on clinically important renal outcomes is possible. The SONAR trial aims to establish whether atrasentan confers renal protection.